Pancasila sebagai Ideologi Negara dalam Kehidupan Berbangsa dan Bernegara - Yohana Fransiska Sirait; Dina Octavia Siburian; Maysaroh Daulay; Theresia Siagian; Putri Sari Margaret Julianty Silaban (Lembaga Pengembangan Kinerja Dosen, 2026)
As the foundation and official ideology of the Indonesian state, Pancasila plays a crucial role in guiding the management of national affairs and the overall conduct of state life. The core principles of Pancasila divinity, humanism, unity, democracy, and social justice reflect the character, identity, and collective values of the diverse Indonesian people. The purpose of this study is to examine in depth the function of Pancasila as a state ideology and the significance of implementing its principles in contemporary and evolving society. Through the exploration and analysis of various scholarly sources, including books, academic journals, and official state documents, this research employs a qualitative approach using a literature review method. The findings indicate that Pancasila functions not only as the nation’s way of life but also as the philosophical foundation of the state and a unifying ideology within Indonesia’s heterogeneous society. Furthermore, the preservation of national identity, the strengthening of social cohesion and peace, and the ability to face the challenges of industrialization and globalization are highly dependent on the successful internalization of Pancasila’s values. Therefore, to achieve sustainable and inclusive national development, consistent and continuous efforts are required to enhance understanding, appreciation, and implementation of Pancasila’s values across all levels of society.